AJARAN DASAR TENTANG ALLAH TRITUNGGAL: DINAMIKA KEBERADAANNYA SECARA TEOLOGIS DAN SIGNIFIKANSI BAGI IMAN - Jacob Messakh (STT Bethel The Way, 2019)
The basic teachings of the Trinity concerning the existence of God in the passage of time and events leave room for debate. Until this day there was a different emphasis between the Eastern churches and the Western churches. The Western Church is enthusiastic about making a cross with Aristotle's philosophy, while the Eastern church continues to emphasize the dynamics of God's existence relatively. This study traces an important point about this difference, especially in understanding the existence of God in terms of three dimensions: a. historical events concerning the presence of God, b. the development of news content that is experiencing changes susbtantif and c. the imposition of interpretation of the news content based on a philosophical point of view. The results are seen that when Aristotle's philosophy was imposed on the existence of God in existence because the plan of salvation to humans had been reduced especially in the strict absolute priority of the existence of God.